2007
DOI: 10.1590/s0102-09352007000500002
|View full text |Cite
|
Sign up to set email alerts
|

Aspectos histopatológicos da adenomiose em úteros bovinos nas diferentes fases do ciclo estral

Abstract: RESUMORelacionaram-se as características da adenomiose com as fases do ciclo estral em 61 peças de úteros de bovinos colhidas em matadouros. A adenomiose foi classificada em superficial e profunda. A fase do ciclo estral foi estimada pela morfologia, pela coloração e pela vascularização do corpo lúteo e presença ou não de folículos ovarianos maiores que 8mm. Os animais que estavam em anestro (n=11) apresentaram a menor ocorrência de adenomiose (8,2%), e os que estavam na fase lútea média (n=21), a maior (31,0%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
4
0
1
Order By: Relevance
“…This study was approved by ethics committee (# 863). This is a retrospective study using samples (0.5 cm 3 ) of the middle-third of the uterine horn collected from 50 post-pubertal, nonpregnant cows, at a local abattoir (near Rio de Janeiro, Brazil), between March/2003 and December/2004 [13]. Samples were fixed in 10% buffered formalin, paraffin-embedded and stored since 2004.…”
mentioning
confidence: 99%
“…This study was approved by ethics committee (# 863). This is a retrospective study using samples (0.5 cm 3 ) of the middle-third of the uterine horn collected from 50 post-pubertal, nonpregnant cows, at a local abattoir (near Rio de Janeiro, Brazil), between March/2003 and December/2004 [13]. Samples were fixed in 10% buffered formalin, paraffin-embedded and stored since 2004.…”
mentioning
confidence: 99%
“…Previous studies (Moreira et al 2007) have observed that during the luteal phase the incidence of adenomyosis as well as the degree of infiltration of the adenomyotic focus were more substantially increased, which suggests the influence of progesterone in the depth the focus may reach. This suggests an intensification of adenomyosis during the luteal phase, as well as a possible regression during the follicular phase.…”
Section: Discussionmentioning
confidence: 79%
“…In bovines, the adenomyosis has been less frequently reported (Moreira et al 2007). The mechanisms of adenomyosis progression have not been fully elucidated, though studies have indicated that this dystrophy is caused mostly by degradation and abnormal reconstitution of uterine elements adjacent to the endometrial-myometrial border due to the differences in MMPs and TIMPs activities, which allows endometrial tissue to invade the myometrium Matsuda et al 2001;Hirata et al 2002;Yang et al 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apesar de já relatada em várias espécies, a sua etiologia ainda não está bem elucidada, e sua ocorrência é considerada pouco frequente em animais domésticos, sendo mais comum em fêmeas que apresentam ciclo menstrual (Greaves e White, 2006;Moreira et al, 2007).…”
unclassified